Awareness of Smoking among Medical Staff in KSA - Manal Abdulaziz Murad; Hoda Jehad Abousada; Raghad Khalid Aljuaid; Amal Saud Almaqati; Rawan Saleh Alotibi; Anas Ali Alzahrnai; Matuq Abdulrahman M Zamzama; Jabr Nahar Bin Jabr Alsulami; Sarah A. Alghabban; Amirah Saad Algethami; et al. (International Journal of Innovative Research in Medical Science, 2020)
Among most medical staff, Smoking is very common and, in this research, we aim To Determine awareness of smoking in medical staff, smoking differences between gender and nationality in KSA. Then we overviewed the rates of smoking in different age groups in the general population. We want also to know the connection of this awareness to smoking or quitting, which may cause future plans that provide for the shedding of light on psychological treatment and mental persuasion to help quit smoking. These study participants were Medical workers from Saudi Arabia and the results may not be applied to different sittings due to differences in facilities and work conditions. Conclusion: It is evident through the results that smoking is very common among doctors, especially men, and smoking is more common among people over 55 years of age than others. In addition to these negatives, most of the sample is aware of the negative aspects of smoking and its risks in the future, but the majority of them still smoke.